Analysis of Public Satisfaction with Population Administration Services in Banyuresmi District: An Expectancy Disconfirmation Theory Approach Using Structural Equation Modeling - Sugiarto Sugiarto; Gugun Geusan Akbar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study analyzes public satisfaction with population administration services in the Banyuresmi District using Expectancy Disconfirmation Theory (EDT). The research model examines the influence of expectation (EX), performance perception (PK), and confirmation/disconfirmation (KD) on satisfaction (KP) using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that confirmation/disconfirmation serves as the primary mediator in the relationship between expectation and satisfaction and between performance perception and satisfaction. Performance perception has the most significant impact on satisfaction compared to initial expectations. These findings suggest improving service quality, speed, and transparency can enhance public satisfaction. However, this study has limitations, including a restricted research area and a quantitative approach that has not explored the subjective aspects of user experience. Future research should conduct comparative studies in multiple regions, use qualitative methods, and incorporate external variables such as government regulations and digital literacy to gain a more comprehensive understanding. Thus, this study provides a foundation for improving policies and enhancing the quality of population administration services.